Field practices for wastewater use in agriculture : future trends and use of biological systems - Tripathi, Vinod K.; Goyal, Megh Raj (Palm Bay, FL : Apple Academic Press, Inc. ; Boca Raton, FL : CRC Press, 2021)
"Field Practices for Wastewater Use in Agriculture: Emerging Issues, Future Trends, and Use of Biological Systems discusses the growing importance of wastewater application in the field of agriculture. Addressing the tremendous need for the irrigation sector to reduce the demand for freshwater in agriculture, this volume looks at wastewater as a source for agricultural irrigation. The volume is divided into four sections: current and emerging issues in wastewater use in agriculture, wastewater management with biological systems, effective field practices for wastewater use, and case studies that provide information on scientific analytical studies on the environment under the influence of wastewater quality from different pollution sources. This book sheds light on the vast potential of wastewater use in agricultural irrigation while also considering safety of the agricultural products for human consumption. Much emphasis has also been given to technological aspects for the treatment of wastewater to protect our environment for better public health protection. Key features: Provides information to planners and policymakers through case studies, offers solutions for the treatment of wastewater generated from different sources, considers sustainability issues and the protection of the environment, examines the issue of water quality from certain sources and with specific techniques."--
Water Footprints of Sustainable Agriculture: An Appropriation of Fresh and Wastewater / Shweta Upadhyay and A.S. Raghubanshi -- Heavy Metal Accumulation in Crops: Status, Sources, Risks, and Management Strategies / Mayuri Chabukdhara, Sanjay K. Gupta, and Arvind K. Nema -- Wastewater Use in Agriculture: An Emerging Issue and Current and Future Trends / Vinod Kumar Tripathi and Ashish Kumar -- Microorganism-Based Biological Agents in Wastewater Treatment: Potential Use and Benefits in Agriculture / Djadouni Fatima -- Biosorption of Heavy Metals by Cyanobacteria from Textile Effluents / B. Jeberlin Prabina, K. Kumar, and N.O. Gopal -- Water Quality Improvement: Use of Indigenous Plant Materials / S. Sivaranjani and Amitava Rakshit -- Impact of Biofilm on Clogging of Drip Irrigation Emitters / Nivedita Khawas, Vinod K. Tripathi, and Anil Kumar -- Sustainable Soil Conservation and Management: Principles, Issues, and Strategies / Shrikaant Kulkarni -- Ex-Situ and In-Situ Crop Residue Management Technologies in Tropical Countries / Pebbeti Chandana, Y. Lavanya, and K. Kiran Kumar Reddy -- Analysis of Groundwater Level: Groundwater Modeling Using GIS in Kolkata / Sushobhan Majumdar -- Disposal of Effluents From Pulp and Paper Industries Through Irrigation / Ajay Bharti and Pankaj K. Pandey -- Correlation Analysis of Municipal Sewage Discharge in River Ganges (Varanasi, India) / Garima Jhariya, Devendra Mohan, and Ram Mandir Singh -- Mapping of Normalized Difference Dispersal Index for Groundwater Quality Study on Parameter-Based Index for Irrigation: Kanchipuram District, India / Kishan S. Rawat, Vinod K. Tripathi, Sudhir K. Singh, and Sushil K. Shukla -- Runoff and Sediment Estimation Using ANN and ANFIS: Case Study of Godavari Basin, India / Ashish Kumar, Pravendra Kumar, and Vinod K. Tripathi.
OCLC-licensed vendor bibliographic record.
Keywords: Sewage irrigation; Sewage -- Purification; Sustainable agriculture; Biotechnology; SCIENCE / General; SCIENCE / Life Sciences / Biological Diversity; TECHNOLOGY / Agriculture / General